Beginning Java EE 5 - Mukhar, Kevin (Apress, 2012)
We, the authors, have read a lot of books on designing and developing software—some better than others—and have spent a lot of time and money in the process. We had some very specific thoughts as we put this book together. The authors of this book are software engineers first. Like you, we have more projects than time to do them in, and we understand that you don’t have time to waste when it comes to learning new technologies. We hope the result of our efforts here is a book that you will pick up frequently, highlight, bookmark, and consider a valued addition to your development resources. First and foremost, the focus of this book is on the practical aspects of getting started with developing distributed software for Java Platform, Enterprise Edition (Java EE). Enterprise Java is a broad and deep subject, and getting started can be like taking a drink from a fire hose. We wanted to put together a practical approach to getting started and spend most of our time talking about the topics that you’ll use 90% (or more) of the time. We are serving up meat and potatoes here.